PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, PELATIHAN DAN EFEKTIVITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDU PADA LEMBAGA PERKREDITAN DESA (LPD) DI KABUPATEN BADUNG - I Gede Wira Andika; Ni Komang Sumadi (UNHI Press, 2021)
Village Credit Institutions (LPD) are financial institutions that help deal with credit problems in the community. The performance of each individual is needed in the management of the Village Credit Institution (LPD). Individual performance is the result of a person's work or expertise to carry out something successfully and efficiently both in quantity and quality in a company. The purpose of this study is to determine the influence of the use of information technology, training and effectiveness of accounting information systems on individual performance. This research was conducted at the Village Credit Institution (LPD) in Badung Regency which has a healthy category with a total of 53 LPD. Data collection techniques in this study used a questionnaire distributed to respondents. Respondents of this research are the head, treasurer, secretary, and savings division who work at the Village Credit Institution (LPD) in Badung Regency. The method used in sampling was purposive sampling method, is determination of the sample based on the suitability of certain characteristics in order to obtain as many as 212 respondents. The data analysis technique used is multiple linear regression with the help of SPSS 21 for Windows. Based on the results of data analysis, it was found that the use of information technology had no effect on individual performance because most of the LPD employees were over 51 years of age who were less able to take advantage of the technology that was currently developing. Meanwhile, training and the effectiveness of accounting information systems have a positive effect on individual performance.